Potentially inappropriate prescribing in a falls clinic using the STOPP and START criteria - Rosalind, Chiam; Nor'izzati, Saedon; Khor, Hui Min; Sukanya, A/P Subramaniam; Siti Sakinah, Binti Mohmad Nasir; Noor Fatin Izzati, Binti Abu Hashim; Tan, Maw Pin * (Springer, 2022)
Background Potentially inappropriate prescribing is increasingly common in older patients with falls. However, published indicators to assess inappropriate prescribing remains unestablished in many countries. Objective This study determined the burden and profile of potentially inappropriate prescribing among patients attending a falls clinic using the STOPP/START criteria and evaluated the factors for falls potentially associated to inappropriate prescribing. Setting University of Malaya Medical Centre Falls Clinic. Method Data of individuals aged ≥ 65 years referred to the falls and syncope clinic were extracted from the falls registry. Potentially inappropriate prescribing was determined with the STOPP/START version 2 criteria. The relationship between potentially inappropriate prescribing with polypharmacy (≥ 5 medications), comorbidities and clinical variables were determined using Pearson's chi-square and potential confounders adjusted for with multivariate regression. Main outcome measure Potentially inappropriate medicines and/or omitted medicines using STOPP/START criteria. Results Data from 421 individuals, aged 77.8 ± 6.7 years and 53.4% women, were included. Potentially inappropriate prescribing was present in 311 (73.9%). Potentially inappropriate medicines use accounted for 84.6% of the 325 prescriptions. 361/659 instances (54.8%) were falls-risk-increasing drugs, with vasodilators (49.3%) being the main potentially inappropriate medicine identified. Of the 177/421 with polypharmacy, 169/177 (95.5%) were exposed to ≥ one potentially inappropriate medicine. 129 instances of potentially omitted medicines were observed in 109 prescriptions (25.9%). Conclusion STOPP/START criteria are useful to identify potentially inappropriate prescribing at the falls and syncope clinic. This finding has important implications for medication review strategies at falls clinic. Future research should determine whether identifying potentially inappropriate prescribing may reduce adverse falls outcomes among patients in this setting.